Molecular diagnostics of gliomas: the clinical perspective - Tabatabai, Ghazaleh; Stupp, Roger; Bent, Martin J. van den; Hegi, Monika E.; Tonn, Jörg C.; Wick, Wolfgang; Weller, Michael (Acta neuropathologica, 2010)
Significant progress has been made in the molecular diagnostic subtyping of brain tumors, in particular gliomas. In contrast to the classical molecular markers in this field, p53 and epidermal growth factor receptor (EGFR) status, the clinical significance of which has remained controversial, at least three important molecular markers with clinical implications have now been identified: 1p/19q codeletion, O6-methylguanine methyltransferase (MGMT) promoter methylation and isocitrate dehydrogenase-1 (IDH1) mutations. All three are favorable prognostic markers. 1p/19q codeletion and IDH1 mutations are also useful to support and extend the histological classification of gliomas since they are strongly linked to oligodendroglial morphology and grade II/III gliomas, as opposed to glioblastoma, respectively. MGMT promoter methylation is the only potentially predictive marker, at least for alkylating agent chemotherapy in glioblastoma. Beyond these classical markers, the increasing repertoire of anti-angiogenic agents that are currently explored within registration trials for gliomas urgently calls for efforts to identify molecular markers that predict the benefit derived from these novel treatments, too.